2004
DOI: 10.1097/01.ta.0000066181.50879.7a
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Aminoguanidine in Behavioral Changes after Blast Injury

Abstract: It is thus suggested that AG could play a neuroprotective role in rats subjected to blast exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 32 publications
1
61
1
Order By: Relevance
“…52 The studies reported here, which were conducted using general anesthesia, however, suggest that a blast-related mTBI exposure can induce PTSD-related traits independent of exposure to a PTSD stressor. Unlike in some other studies, 5,26,31,33,34,36,38,43,[47][48][49][50] we did not see cognitive effects. No deficits were present in a Morris water maze or in a win-shift task, a relatively challenging test of working memory.…”
Section: Figcontrasting
confidence: 54%
See 3 more Smart Citations
“…52 The studies reported here, which were conducted using general anesthesia, however, suggest that a blast-related mTBI exposure can induce PTSD-related traits independent of exposure to a PTSD stressor. Unlike in some other studies, 5,26,31,33,34,36,38,43,[47][48][49][50] we did not see cognitive effects. No deficits were present in a Morris water maze or in a win-shift task, a relatively challenging test of working memory.…”
Section: Figcontrasting
confidence: 54%
“…33 These studies have documented a variety of, at least, short-term effects, suggesting that blast can be associated with anxiety as well as impairments in a variety of learning and memory tasks. 5,26,31,34,36,43,47,49,50 One study also reported impairments in prepulse inhibition immediately after blast exposure, changes that had mostly recovered by 90 days after exposure. 38 We utilized a rat model of mTBI in which adult male rats were exposed to a controlled blast overpressure injury in a shock tube.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microglial activation was particularly pronounced in the superficial regions of the cerebral and cerebellar cortex. Performance on motor tasks in rats was impaired after exposure to primary blast explosions [24]. These investigators also reported degeneration of neurons in the cerebral cortex.…”
Section: Experimental Animal Studies On Blast-related Brain Injurymentioning
confidence: 74%